AB0709 The relationships between thoracic region involvement and functions of upper extremity, scapular kinematics in patients with ankylosing spondylitis: pilot study. (15th June 2017) - Mete, O; Oskay, D; Tufan, A
Abstract : Background: Ankylosing spondylitis (AS) is a chronic inflammatory rheumatic disease that mainly affects the axial skeleton. As the disease progresses, increased thoracic kyphosis can be seen in these patients. Because of increase in thoracic kyphosis, the orientation of the scapula on the thorax and thus the functions of upper extremity may change. Objectives: The aim of the study is to investigate the relationships between thoracic region involvement and functions of upper extremity, scapular kinematics in patients with AS. Methods: Fifteen (15) patients with AS and eleven (11) healthy control were participated in the study. Thoracic kyphosis angle and shoulder range of motions were assessed by using digital inclinometer, scapular and shoulder muscle strength were assessed by using digital dynamometer, three dimensional (3D) scapular kinematics were assessed by using electromagnetic tracking system, disability level of upper extremity were assessed by Turkish Version of Disability of Arm, Shoulder and Hand Questionnaire (DASH-T). Spearman correlation coefficient, Pearson correlation coefficient, Mann-Whitney U Test and Independent Sample T-test were used for statistical analysis. Results: DASH-T, thoracic kyphosis angle, shoulder abduction, internal rotation, external rotation of dominant side, shoulder abduction, internal rotation of non-dominant side, anterior deltoid, middle deltoid, serratus anterior, downward trapezius muscle strengths of dominant and non-dominant side, upward rotation of scapula during 30, 60, 90 degrees humerothoracic elevations at sagital plane of dominant and non-dominant side showed significantly differences between two groups. Thoracic kyphosis angle showed correlations with DASH-T (p<0, 05, r:0, 619), shoulder flexion, abduction, internal rotation, external rotation of dominant side (p<0, 05, r:-0, 867), (p<0, 05, r:-0, 580), (p<0, 05, r:-0, 657), (p<0, 05, r:-0, 599) and shoulder flexion, abduction, internal rotation of non-dominant side (p<0, 05, r:-0, 813), (p<0, 05, r:-0, 665), (p<0, 05, r:-0, 741), respectively. Thoracic kyphosis angle showed correlations with anterior deltoid, middle deltoid, serratus anterior, middle trapezius, downward trapezius muscle strengths of dominant side and non-dominant side, respectively (p<0, 05, r: -0, 899), (p<0, 05, r:-0, 854), (p<0, 05, r:-0, 805), (p<0, 05, r:-0, 791), (p<0, 05, r:-0, 633), (p<0, 05, r:-0, 877), (p<0, 05, r:-0, 796), (p<0, 05, r:-0, 884), (p<0, 05, r:-0, 724), (p<0, 05, r:-0, 673). Correlations between thoracic kyphosis angle and anterior tilt of scapula during 90 degree humerothoracic elevations at sagital plane of dominant side were obtained (p<0, 05, r:0, 522). Conclusions: Scapulothoracic joint biomechanics and functions of upper extremity were affected by kyphotic posture in patients with AS. One of the most important causes of biomechanical impairment in AS patients is the deterioration of scapular kinematics with kyphosis. For preventing functional impairment, treatment programs should be supplemented with scapular kinematic exercises. References: Braun (2007). Ankylosing spondylitis. The Lancet. Kebaetse (1999). Thoracic position effect on shoulder range of motion, strength, and three-dimensional scapular kinematics. Archives of physical medicine and rehabilitation. Disclosure of Interest: None declared